Communication skills in the training of psychiatrists: A systematic review of current approaches. (July 2017) - Ditton-Phare, Philippa; Loughland, Carmel; Duvivier, Robbert; Kelly, Brian
Objectives: A range of communication skills training programmes have been developed targeting trainees in various medical specialties, predominantly in oncology but to a lesser extent in psychiatry. Effective communication is fundamental to the assessment and treatment of psychiatric conditions, but there has been less attention to this in clinical practice for psychiatrists in training. This review examines the outcomes of communication skills training interventions in psychiatric specialty training. Methods: The published English-language literature was examined using multiple online databases, grey literature and hand searches. The review was conducted and reported using Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Studies examining the efficacy of communication skills training were included. Randomised controlled trials, pseudo-randomised studies and quasi-experimental studies, as well as observational analytical studies and qualitative studies that met criteria, were selected and critically appraised. No limits were applied for date of publication up until 16 July 2016. Results: Total search results yielded 2574 records. Of these, 12 studies were identified and reviewed. Two were randomised controlled trials and the remaining 10 were one-group pretest/posttest designs or posttest-only designs, including self-report evaluations of communication skills training and objective evaluations of trainee skills. There were no studies with outcomes related to behaviour change or patient outcomes. Two randomised controlled trials reported an improvement in clinician empathy and psychotherapeutic interviewing skills due to specific training protocols focused on those areas. Non-randomised studies showed varying levels of skills gains and self-reported trainee satisfaction ratings with programmes, with the intervention being some form of communication skills training. Conclusion: The heterogeneity of communication skills training is a barrier to evaluating the efficacy of different communication skills training programmes. Further validation studies examining specific models and frameworks would support a stronger evidence base for communication skills training in psychiatry. It remains a challenge to develop research to investigate behaviour change over time in clinical practice or to measure patient outcomes due to the effects of communication skills training.